Conservation of land snails in the mountain grasslands of the Argeninian pampas - Delhey, Valdemar Kilian (2005)
The Ventana Mountains are not only a remarkable physical feature within a mostly plains region, but also a ‘biodiversity island’ in the Pampas, the region most modified by agricultural activities in Argentina. These mountains harbor both endemic land snails and species of the surrounding plains. Thus, this is the most important area for land snail conservation in the Pampas, a region with a rather poor overall diversity of terrestrial snails. The state park ‘Parque Provincial Ernesto Tornquist’ (PPET) is the only reserve protecting these unique grasslands. Major threats to the native biota of the park are biological invasions by feral horses and exotic pines, which could also be affecting land snail specific goals was to investigate the effect of environmental conditions and the possible impact of horses on the distribution and abundance of four autochthonous macrosnail species: Austroborus lutescens dorbignyi (Doering, 1876), Discoleus aguirrei (Doering, 1884), Plagiodontes patagonicus (d’Orbigny, 1835) and the strictly endemic Ventania avellanedae (Doering, 1881). Sampling was carried out at two geographical scales. Environmental conditions recorded included topography, habitat structure, vegetation physiognomy, climatic and edaphic factors, floristic composition and horse impact.